Enhanced Efficiency of PTB7 : PC61BM Organic Solar Cells by Adding a Low Efficient Polymer Donor - Joana Farinhas; Ricardo Oliveira; Quirina Ferreira; Jorge Morgado; Ana Charas (International Journal of Photoenergy)
Ternary blend polymer solar cells combining two electron-donor polymers, poly[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl] (PTB7) and poly[2,5-bis(3-dodecylthiophen-2-yl)thieno[3,2-b]thiophene] (pBTTT) and [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM), as electron-acceptor, were fabricated. The power conversion efficiency of the ternary cells was enhanced by 18%, with respect to the reference binary cells, for a blend composition with 25% (wt%) of pBTTT in the polymers content. The optimized device performance was related to the blend morphology, nonrevealing pBTTT aggregates, and improved charge extraction within the device.